Unveiling the heterogeneous impacts of export product diversification on renewable energy consumption: New evidence from G-7 and E-7 countries. (February 2021) - Shahzad, Umer; Lv, Yulan; Doğan, Buhari; Xia, Wanjun
Abstract: One of the core objectives in Sustainable Development Goals of developed and emerging economies is to enhance the renewable energy consumption level to overcome environmental challenges. However, little is known about the export product diversification impacts on renewable energy consumption. The prime objective of this study is to explore the effects of export diversification, extensive margin and intensive margins on renewable energy consumption using a panel data of 14 countries (G-7 and E-7) spanning the period of 1990–2017. Current study is based on panel cointegration analysis, FGLS and FMOLS techniques, where the renewable energy consumption is given as a function of export diversification, economic growth, industrialization, trade openness and natural resources. The empirical findings show that product diversification policies have positive effects on renewable energy demand for developed and emerging economies. Interestingly, our results illustrate that the nonlinear hypothesis is valid between export diversification and renewable energy for the sample countries, while the threshold level and direction are different for both panels. Highlights: The impact of export product diversification on renewable energy consumption is examined. G-7 countries and E-7 countries over 1990–2017 are analyzed. Empirical results show that export diversification significantly influence renewable energy consumption. The non-linear hypothesis between export diversification and renewable energy is confirmed for G-7 and E-7 countries. Natural resources and International trade significantly influence renewable energy consumption.